Development of STEAM-Based Video Learning Media for Early Childhood Education with the Inclusion of Religious and Moral Values - Khasanah; Violy, Agita; Eka Yunita Yustantina; Moh. Fahri Yasin (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This article aims to develop video learning media specifically crafted to assist educators in presenting learning materials more tangibly and understandably, particularly within early childhood education. Guided by the Research and Development (R&D) process, the study focuses on two primary objectives: (1) elucidating the intricacies of developing STEAM-based video learning media for Early Childhood Education, incorporating Religious and Moral Values, and (2) evaluating the appropriateness and effectiveness of such media in the educational context. Adopting the ADDIE development model, the research encompasses five pivotal stages: Analysis, Design, Development, Implementation, and Evaluation. The validation process for the developed product entails collaboration with media, material, and design experts, complemented by feedback from colleagues. One-to-one tests, Small Group Tests, and Field Test methods are employed to assess the effectiveness of the media. Validation results from these experts affirm that the developed media aligns seamlessly with the criteria for successful application in educational settings. During the product implementation phase involving 15 students, it became evident that this development was an effective learning tool. The post-test scores surpassing the pre-test scores indicate the product's efficacy in enhancing the understanding of morning phenomena, instilling religious and moral values, and fostering STEAM creativity in early childhood education.